Richness of lichens growing on Eocene fossil penguin remains from Antarctica - García, Renato Andrés (2020)
Antarctica presents one of the most severe environmental conditions for life. Under these circumstances, cryptogams are the dominant photosynthetic organisms, among which we find a great richness of lichens. In Antarctic environments, lichens can grow on rocks or in this case on fossil remains, among the few available substrates. In the present contribution, we examined all fossil penguins of the Antarctic collection of the Museo de La Plata, as a significant sample of fossil vertebrates. The selected materials here described come from the Submeseta Formation (Eocene) on Seymour/Marambio Island, located northeast of the Antarctic Peninsula on the Weddell Sea. Given the scarcity of lichenological studies on this island, and the results presented here add significantly to our knowledge of the lichen species that occur there with the recognition of 11 taxa with a crustose morphology (epilithic and endolithic), the sampling of lichens growing on fossil bones acquired an evident importance.